More, Better or Different? : Investing in Paraguay’s Roads - World Bank (World Bank, Washington, DC, 2021)
Paraguay is a middle-income, landlocked country with a population of about seven million. The nation is highly dependent on its transport and logistics infrastructure to connect to regional markets and international seaports. In road quality and connectivity, on the other hand, Paraguay trails its neighbors and other middle-income countries. According to the Global Competitiveness Indices, Paraguay is in the bottom third of indexed countries for road connectivity and quality. The government has attempted to address perceptions on quality and connectivity through higher budget allocations for the road sector. The higher road sector budget has been directed to expansion and preservation of the paved roads since 2012 and has, on the whole, allocated sufficient funds for their maintenance as estimated by this Public Expenditure Review (PER). Despite this there has been a slight decline in the overall quality of the network due to over and under funding of roads geographically and by functional classification. This PER is structured as follows: Chapter 2 provides some background on the Paraguayan economy, the country’s road network (primary, secondary, and tertiary) features and analysis, and an overview of the government institutions responsible for the network; Chapter 3 describes how Paraguay budgets and manages its road sector, what the funding sources are, and how efficiently the expenditures are being spent; Chapter 4 assesses Paraguay’s goals for its road sector, the effectiveness of its budget execution and sustainability of its funding, and its sector monitoring practices; and Chapter 5 concludes with the main findings and recommendations.